(untitled) (Baghdad Science Journal, 2014)
Regular sampling for six months from January to July 2012 were taken in small, shallow, perennial, standing ponds near the Greater Zab River, Gwer district, Erbil. A variety of physicochemical parameters were determined. Air and water temperature were falling between 15.2 - 34.7 ? C and 15.5 and 26.5 ?C. The waters are neutral (pH 7.38-8.27), hard, alkaline, salty, high in TDS and EC (892-966?S/cm, and rich in nutrients (NO3: 2.1-4.1mg/l, PO4: 0.33-0.62 mg / l , SO4: 24.7-80.2 mg / l ). The attention fixed on a filamentous blue- green algae Glaucospira Lagerheim, 1982) which is new to Iraqi flora. It is a filament (trichome), solitary, pale or yellowish blue – green, without sheath, Screw like coiled, motile, some of them are actively motile. In this study nine species were identified, classified and described with their original and hand drawing, photo vis.; Glaucospira sp.: syn. Spirulina abreviata Lemm. ex Kleb. and Lemm. , G. agilissima Lag., G. laxissima G.S.West syn.: Spirulina laxissima f. major Des., Glaucospira sp. syn.: Spirulina tenuior Lag.,Glaucospira sp. Syn.: Spirulina corakiana Playf., Glaucospira sp.syn.: Sprulina nodosa Scham. Glaucospira sp. syn.: Spilurina baltica Mart.,Glaucospira sp. Syn.: Spirulina magnifica Cop. And Glaucospira sp. syn.: Spirulina subtilissima Mostly they are from Spiralina Turpin ex Gomont.